A new approach to SHRIMP II zircon U-Th disequilibrium dating - Marsden, Ruby C.; Kirkland, Christopher L.; Danišík, Martin; Daggitt, Matthew L.; Ahn, Ung-San; Friedrichs, Bjarne; Evans, Noreen J. (Computers & geosciences, 2022)
U-Th disequilibrium dating of zircon is used to determine the crystallisation age of zircon crystals which formed ≲350 ka. In this work we present a new analytical and data reduction workflow for zircon U-Th disequilibrium analysis using a Sensitive High Resolution Ion MicroProbe (SHRIMP), specifically the SHRIMP II instrument at Curtin University. This is the first zircon U-Th disequilibrium work carried out on the SHRIMP II, and the workflow was investigated with both 3 nA and 6 nA primary beam intensities, using an inverted mass run sequence (from high to low mass). The data reduction was affected by complex background corrections on the 230Th mass peak, extremely low counts on 230Th, and by a logarithmic high mass tail from shouldering mass peaks. A new approach to data reduction and a new computer program (Crayfish) written in Python is presented to address these complexities. Crayfish aids in visualisation of the raw count data from SHRIMP .pd files, allowing for more interaction with raw data during reduction, and formally propagates uncertainties from measurements to age. A case study testing the new approach was undertaken using trachytic samples from Jeju Island, South Korea, an active volcanic field and a UNESCO world heritage site. The newly derived SHRIMP crystallisation ages of 13 ± 27 to 212 ± 324 ka (2σ uncertainties) replicate measurements performed using a CAMECA IMS 1280.